In Situ Transmission Electron Microscopy Study of Nanocrystal Formation for Electrocatalysis. Issue 12 (16th October 2019) - Shi, Fenglei; Li, Fan; Ma, Yanling; Zheng, Feiyu; Feng, Rui; Song, Chengyi; Tao, Peng; Shang, Wen; Deng, Tao; Wu, Jianbo
Abstract: Electrocatalysts play a critical role in electrochemical catalytic processes. In order to rationally design active and durable electrocatalysts, it is crucial to have a deep understanding on the formation mechanism of the electrocatalysts. With the development of in situ transmission electron microscopy (TEM) techniques, it is possible to observe nanoscale behaviors in real‐time to probe the formation of various electrocatalysts. Here, the nucleation, growth, attachment, diffusion, corrosion and other nanoscale dynamics related to the formation of zero‐dimensional (0D), one‐dimensional (1D), and two‐dimensional (2D) nanomaterials are discussed. The current challenges and potential opportunities for in situ techniques towards observation of electrocatalyst formation including high resolution, fast imaging and beam effect are also described. Abstract : With the development of in situ transmission electron microscopy (TEM) techniques, it is possible to observe nanoscale behaviors in real‐time and to probe the formation of electrocatalysts. The nucleation, growth, attachment, diffusion, corrosion and other nanoscale dynamics related to the formation of zero‐dimensional (0D), one‐dimensional (1D), and two‐dimensional (2D) nanomaterials are discussed in this review.